Pre- and postoperative predictors of phantom limb pain - Larbig, Wolfgang; Andoh, Jamila; Flor, Herta (Neuroscience letters, 2019)
Phantom limb (PLP) as well as residual limb pain (RLP) are still a very significant problem after amputation and their causes are only partially known. Here we tested whether the predisposition for the frequency, duration and intensity of PLP and RLP is shared with other prior chronic pains and/or the presence of postamputation subacute pain. A week preoperatively we collected data using validated questionnaires, a pain diary and interviews on past chronic pain conditions, acute pain, depression, anxiety, pain interference, life control, social support and affective distress and pain ratings one day before the amputation in 52 patients scheduled for limb amputation. In the week postamputation and again three and 12 months thereafter, we collected data on postoperative wound pain, PLP, RLP and non-painful phantom sensation (PLS). Phantom and residual limb pain indices were calculated per patient, integrating the intensity, frequency and duration of past chronic pain, PLP, RLP and PLS into a single value to index the overall burden of pain. We report that acute and chronic pain long before but not on the day before the amputation and subacute pain postamputation significantly predicted up to half of the variance in the incidence and severity of PLP, RLP and PLS 12 months postamputation. Moreover, the severity of these painful sensations at 12 months postamputation was partially predicted by preamputation scores of depression and anxiety. These findings corroborate the hypothesis that chronic pain and non-painful sensations following limb amputation are strongly related to longstanding preoperative chronic pain and to subacute postoperative pain as well as to psychological factors before the amputation that may be inherited and/or acquired (learning- and memory-related). Furthermore, we also confirm that subacute pain postamputation comprises an additional risk factor for long-term painful sensations postamputation. Our results suggest that timely interventions might prevent the development of chronic pain.
Available online 29 November 2018
Gesehen am 10.10.2019